Right Heart Chambers Longitudinal Strain Provides Enhanced Diagnosis and Categorization in Patients With Pulmonary Hypertension - Espinola-Zavaleta, Nilda; Antonio-Villa, Neftali Eduardo; Guerra, Enrique C.; Nanda, Navin C.; Rudski, Lawrence; Alvarez-Santana, Ricardo; Camacho-Camacho, Gyssele; Aranda-Fraustro, Alberto; Cossio-Aranda, Jorge; Zamora, Karina; Oregel-Camacho, Diego; Armenta-Moreno, Javier Ivan; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background Increased systolic pulmonary arterial pressure (sPAP) could lead to the mechanical dysfunction and myocardial fibrosis of the right heart chambers. Echocardiographic strain analysis has not been adequately studied in patients with pulmonary hypertension (PH). Study design and methods A cross-sectional cohort of patients with suspected PH and echocardiographic strain evaluation was recruited. The cut-off values of peak tricuspid regurgitation velocity (TRV) with the low probability of PH (≤2.8 m/s), intermediate probability (2.9–3.4 m/s, without other echo PH signs), and high probability of PH (2.9–3.4 m/s with other echo PH signs and >3.4 m/s) categories were studied by right ventricular and right atrial (RA) strain analysis in a sample of 236 patients. Results The results showed that 58 (56.9%) patients had low, 15 (14.7%) had intermediate, and 29 (28.4%) had a high probability of PH. We observed a negative association between right ventricular free wall strain (RV-FWS) and atrial global strain with sPAP. With the increase in PH severity, RA reservoir, conduit, and contraction (booster) strain values decreased. The identified cut-off values of strain parameters had an adequate ability to detect PH severity categories. In addition, the post-mortem biopsies of right heart chambers from subjects with known severe PH were analyzed to quantify myocardial fibrosis. Our sample of right heart biopsies (n = 12) demonstrated an association between increased sPAP before death and right ventricular and RA fibrosis. Conclusion Mechanical dysfunction and fibrosis in the right chambers are associated with increased sPAP. Right ventricular and atrial strain could provide enhancement in the diagnosis and categorization of subjects with suspected PH.